Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1126/science.6344218
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Signal Peptide Cleavage of Escherichia coli Prolipoprotein

Abstract: Oligonucleotide-directed site-specific mutagenesis was applied to alter the cleavage site in the signal peptide of the major outer membrane lipoprotein of Escherichia coli. Replacing the glycine residue at the cleavage site with an alanine residue did not affect the processing of the signal peptide. However, when the same cleavage site was constructed by the deletion of the glycine residue, the signal peptide was no longer cleaved. These results indicate that stringent structural integrity at the cleavage site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Cal protein is translated from the same mRNA as colicin A (23), but it has to interact with modifying enzymes and signal peptidase II which are membrane bound. It has been reported that mutations altering amino acids in the vicinity of (12,18,19,30) and prepenicillinase (14,38) affect the modification, processing, and secretion of these proteins in both E. coli and Bacillus subtilis. Furthermore, various studies have suggested that the overall conformation of preproteins can exert a considerable effect on the rate of modification and processing (for a review, see reference 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cal protein is translated from the same mRNA as colicin A (23), but it has to interact with modifying enzymes and signal peptidase II which are membrane bound. It has been reported that mutations altering amino acids in the vicinity of (12,18,19,30) and prepenicillinase (14,38) affect the modification, processing, and secretion of these proteins in both E. coli and Bacillus subtilis. Furthermore, various studies have suggested that the overall conformation of preproteins can exert a considerable effect on the rate of modification and processing (for a review, see reference 38).…”
Section: Discussionmentioning
confidence: 99%
“…Inouye et al (19) have shown that replacing the consensus sequence Leu-Ala-Gly-Cys with Leu-Ala-Ala-Cys does not affect the synthesis, processing, or export of the lipoprotein. It has been previously demonstrated that the Cal protein undergoes a particularly slow processing accompanied by accumulation of the signal peptide and that the mature form is partly released to the spent medium with colicin A (7).…”
mentioning
confidence: 99%
“…This sequence conforms favorably to the consensus sequence for lipid modification of gram-negative bacterial lipoproteins (4,10,26 (4,26). If so, the Cys-20 residue of the 17K antigen would be modified through a thio-ester linkage with glycerol, which would subsequently be modified by the addition of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The deduced amino acid sequence of the 17K antigen contained the residues Leu-Gln-Ala-Cys at positions 17 to 20. This sequence is strikingly similar to the consensus sequence Leu-Ala(Gly)-Gly(Ala)-Cys for lipid modification in E. coli (4,10,26) harboring the plasmid vector pKK223-3 was used as the source of radiolabeled protein (Fig. 5A, lane C).…”
mentioning
confidence: 99%
See 1 more Smart Citation